Peningkatan Kemampuan Pedagogik Guru melalui Program Pelatihan dan Pendampingan Bekelanjutan dalam Pembelajaran Computational Thinking pada Mata Pelajaran Matematika - Dyah Susilowati; Apriani Apriani; Kartarina Agustin; Ni Gusti Ayu Dasriani (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
The problem faced by target partners (target schools) is the low ability of students to solve problems. In fact, problem solving ability is one of the skills that must be possessed in the 21st century. This community service aims to improve teacher pedagogical competence in implementing Computational Thinking learning as well as assistance in its implementation. The method used is an educational approach with stages, identification of target schools, socialization of activities, implementation, monitoring and evaluation. The result of this activity was an increase in teacher knowledge in computational thinking by 95%, and teacher interest in applying computational thinking to subjects by 92%. The conclusion of this activity is known that community service partners have increased their knowledge of problem solving methods using a computational thinking approach and can apply them in mathematics learning.